Distribution of fluid flow pressure through tandem square cylinders with the addition of triangular cylinder as a disturbance object. Issue 1 (August 2021) - Habiba, Syahrir; Salam, Nasaruddin; Tarakka, Rustan; Jalaluddin,; Ihsan, Muhammad
Abstract: Flow across a square cylinder in a tandem arrangement is a shape characterization that is often used in structural engineering, transportation, and heat exchangers, where wind and water loads are one of the main factors that need to be considered in the design because they are associated with loss of energy. This is a problem faced by various industries in increasing the efficiency and stability of their systems. To reduce this energy loss, flow modification can be carried out in the form of adding disturbance objects that are placed in the front area of the main object, so that the fluid flow can pass through the object without any flow separation and produce a uniform flow after passing through the object. The research objective is focused on analyzing the effect of adding a triangular cylinder as a disturbance object to the characteristics of the flow pattern and the pressure distribution on the walls of the square cylinder in a tandem arrangement. This research used numerical computation methods and was validated through experimental testing at an upstream velocity of 19 m/s. The hydraulic diameter of the disturbance object was determined to be 0.033 m and the distance ratios M/D were 0.05, 0.15, 0.25, 0.35, 0.45, and 0.55, respectively. The results showed that the application of a triangular cylinder as a disturbance object had an effect on the characteristics of the flow pattern and the pressure coefficient, where the lowest pressure coefficient on the front side and the highest pressure coefficient on the side and rear sides were obtained in a model with a distance ratio M/D = 0.45.